Tritium-Labeled Compounds IX. Determination of Isotope Effects in Reactions Yielding Water-t from Nonvolatile Reactants. Oxidation of Aldoses-1-t With Iodine - Isbell, Horace S. (J Res Natl Bur Stand A Phys Chem, 1963)
A convenient method is presented for estimating isotope effects in reactions which yield water-t. The water-t is separated by freeze-drying, and k*/k is calculated from the extent of the reaction and the ratio of the radioactivity of the water-t to that of the initial reactant. Application of the method to the oxidation of aldoses-1-t at 25 °C with iodine in alkaline solution gives values for k*/k ranging from 0.12 to 0.17, with an average of 0.14. There are no significant differences in the values of k*/k obtained for aldoses differing in configuration, or for pentoses and hexoses. The isotope effect corresponds to a ratio of one to seven for the respective rates of reaction of the labeled and unlabeled molecules.